The Influence of Time Value, Price Perception, and Service Quality on The Intention to Repurchase Tickets on Passenger Roro Ships - Asep Suparman; Zahra Fajardini; Totok Sugiharto (Pusat Penelitian dan Pengabdian kepada Masyarakat Sekolah Tinggi Ilmu Ekonomi Trisakti, 2022)
Repurchase intention in the many transportation options in Indonesia is interesting to study. This study aims to determine the factors that will influence consumers to buy back tickets from shipping companies, namely passenger Roro Ships. This research is a research using a quantitative approach by distributing surveys to passengers on Roro Ships. The sampling technique used is purposive sampling. The analysis technique used is the Partial Least Square technique, using SmartPLS as a tool to process data. The results of the research test show that the time value coefficient and service quality do not affect the repurchase intention of the Roro Passenger Ship passengers, but the price perception will greatly affect the repurchase intention of the Roro Passenger ship passengers. Simultaneously the variables of time value, price perception and service quality greatly affect customer repurchase intention.